Influence of the Size of the Field of View on Visual Perception While Running in a Treadmill-Mediated Virtual Environment - Caramenti, Martina; Pretto, Paolo; Lafortuna, Claudio L.; Bresciani, Jean-Pierre; Dubois, Amandine (Frontiers in Psychology, 2019)
We investigated how the size of the horizontal field of view (FoV) affects visual speed perception with individuals running on a treadmill. Twelve moderately trained to trained participants ran on a treadmill at two different speeds (8 and 12km/h) in front of a moving virtual scene. Different masks were used to manipulate the visible visual field, masking either the central or the peripheral area of the virtual scene. The participants were asked to match the visual speed of the scene to their actual running speed. For each trial, participants indicated whether the scene was moving slower or faster than they were running. Visual speed was adjusted according to the responses using a staircase method until the Point of Subjective Equality was reached, that is until visual and running speed were perceived as matching. For both speeds and all FoV conditions, participants underestimated visual speed relative to the actual running speed. However, this underestimation was significant only when the peripheral FoV was masked. These results suggest that the size of the field of view should absolutely be taken into account for the design of treadmill-mediated virtual environments.